Раскрыть скобки.  a+(-3b)+(-c)+d   (-6x)+(-7y)+z(-m)+(-4n)+(-3p)(-0,6a)+(-b)+c+(-3d)(-x)+6y+(-5z)m+(-3n)+8pвынести общий множитель за скобки mn-m; 4,5m+1,5n ;   abc+ab

Раскрыть скобки.  a+(-3b)+(-c)+d    (-6x)+(-7y)+z (-m)+(-4n)+(-3p) (-0,6a)+(-b)+c+(-3d) (-x)+6y+(-5z) m+(-3n)+8p вынести общий множитель за скобки mn-m; 4,5m+1,5n ;   abc+ab
Гость
Ответ(ы) на вопрос:
Гость
Раскрыть скобки.  a+(-3b)+(-c)+d = a-3b-c+d (-6x)+(-7y)+z = -6x-7y+z (-m)+(-4n)+(-3p) = -m-4n-3p (-0,6a)+(-b)+c+(-3d) = -0,6a-b+c-3d (-x)+6y+(-5z) = -x+6y-5z m+(-3n)+8p = m-3n+8p вынести общий множитель за скобки mn-m; = m(n-1) 4,5m+1,5n = 1,5(3m+n) abc+ab = ab(c+1)
Не нашли ответ?
Ответить на вопрос
Похожие вопросы